Systematic Mapping of the Foreign Exchange Rate-Stock Market Relationship using Bibexcel and VOSviewer (IITM Journal of Business Studies, 2024)
Empirical research work has been done to  comprehend the relationship between foreign  exchange rates and the stock market. This  review article provides a proper framework for  the published work in this research area. The  published research work is collected from the  Scopus database, and bibliometric analysis is  done using Bib Excel and VOS viewer. Apart  from getting bibliometric results of the collected  data, the findings of most cited papers are also  piled up. The mixed findings of the published  articles confirm the existence of a significant  relationship between the stock market and  foreign exchange rate. Still, the robustness of  connection is highly dependent on the economic  particulars of any country. It is also analyzed  that the relationship appears more potent in the  crisis period. This systematic analysis facilitates  researchers to focus on this research area to get  a more specific conclusion in this research area.
Keywords: Foreign exchange rate; Stock market; Bibliometric; Bib Excel; VOS viewer; Systematic analysis.